The Influence of Financial Literacy And Risk-Taking Behavior on Entrepreneurial Performance Mediated By Market Expansion - Agreianti Puspitasari; Ni Komang Septia Noriska; Topan Setiawan (Jurnal Mamangan, 2025)
It is recorded at the Coordinating Ministry for Cooperatives and SMEs that the number of micro businesses has reached 63.96 million, businesses small businesses reached 193,959, and small businesses medium enterprises reached 44,728. The difference in the number of micro- enterprises, medium-sized enterprises small, and business This fairly large middle class shows that there is still at least MSME entrepreneurs, especially micro-entrepreneurs, are not yet brave enough to expand their businesses. Business expansion is influenced by several factors, one of which is consumer behavior. MSME entrepreneurs in taking risks. This is in line with the perspective businessman Where high risk high return. This paradigm is very interesting to observe and empirically test how the behavior of Micro entrepreneurs in taking risks have an impact on the implementation of the business expansion strategy that will be carried out.Many previous studies have examined risk - taking behavior. However Not yet Some measure its impact on business expansion strategies. In previous research, Risk Taking Behavior was only discussed in terms of the risk profile of entrepreneurs, without looking at the factors that influence risk-taking decisions from entrepreneurs to form Risk-taking characteristics. Risk-taking behavior in this research is linked to the business expansion strategies implemented by micro- entrepreneurs. This test is based on the perspective that every business expansion carries risks, which must be addressed. taken into account by entrepreneurs to reduce its impact on the business being run. In this study, the indicators that will be used to see the variables from Risk Taking Behavior is knowledge and ability micro entrepreneurs in running their businesses, the framework thinking, each individual's preference for risk, each individual's perception of risk, organizational culture and structure, family member involvement, gender, characteristics Personality, self -confidence, self -reflection, self -control, anxiety in taking risks, and individual relationships with business partners. Meanwhile, the indicator for identifying factors influencing internal business expansion strategies is knowledge. micro entrepreneurs towards financially. Micro entrepreneurs need to know how much power financially to make a decision its expansion.This research is a assessment quantitative experimental studies between subjects. Where the data to be used is primary data obtained by distributing questionnaires and also secondary data obtained from various sources such as websites, books, and journals. Data processing in this study will use the Structural Equation Model (SEM). The SEM model developed in this study is an SEM model with indicators formative. Where the indicators in this research are factors that influence the variables latent. Data for each indicator in each variable will be collected using a questionnaire using a scale likert. Any data obtained Then Then will processed using SEM. The results of the SEM model that was developed were then will be translated descriptively so as to get the right approach to see the relationship between these two variables